37.2k views
4 votes
(-3)4= (4)3=

Evaluate
(-3)*4=
(4)*3=

User GSTD
by
4.8k points

2 Answers

6 votes

Answer:

-12

12

Explanation:

(-3) * 4

Remove parentheses. ( -a) = -a

= -3 * 4

Multiply the numbers: 3 * 4 = 12

= -12

(4) * 3

Multiply the numbers.

4 * 3 = 12

= 12

User Chintanparikh
by
5.7k points
3 votes

Answer:

(-3)× 4 = -12

4 × 3= 12

Explanation:

The first expression is


(-3)\cdot4

We can write -3 = -1 × 3


(-1\cdot3)\cdot4

Apply associative property of multiplication


-1\cdot(3\cdot4)

Multiply 3 and 4


-1\cdot(12)\\\\=-(1\cdot12)

Finally, simplify by multiplying the numbers


=-12

The Second expression is

4 × 3

= 12

User Eric Zinda
by
4.6k points